PENGEMBANGAN E-KOMIK PELITA (PERUBAHAN ENERGI LISTRIK UNTUK ANAK) PADA PEMBELAJARAN IPAS KELAS IV SDN 19 PANGKALPINANG - Indrit Wulandari; Feni Kurnia; Fandi Nugroho (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to develop the E-Comic PELITA (Electrical Energy Changes for Children) learning media used in fourth-grade science learning at SDN 19 Pangkalpinang to meet the criteria of validity and practicality. This study uses the Research and Development (R&D) method with a 4D model that includes the stages of defining (defining), designing (designing), developing (developing), and disseminating (disseminating). Data collection techniques were carried out through interviews, distributing questionnaires, and conducting trials on the developed media. The results showed that the E-Comic PELITA obtained a very high level of feasibility. Based on the assessment of media experts, this media obtained a validation score of 90%, while validation from material experts reached 94.1%, so it was declared very valid. In addition, the practicality aspect of the media also showed very good results, with a score of 100% in small group trials and 90.1% in large group trials. Thus, the PELITA E-Comic can be an alternative learning media that is effective, interesting, visual, and contextual in helping elementary school students understand the concept of changes in electrical energy. Keywords: E-Comic, PELITA, 4D Model